Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Menulis Huruf Nama Masing-Masing Anak 5-6 Tahun Tk Imanuel Kedi Halmahera Barat - Jenny I . Dengah; Selfiana Ributu; Meiske E. Tumbel (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to improve children's fine motor skills through the activity of writing the name letters of each child at Kindergarten Imanuel Kedi Halmahera Barat. The background problem of this study is the lack of writing activities to improve children's fine motor skills. In this study the authors used Classroom Action research ( PTK) through 2 cycles through planning, implementation, observation and reflection activities, by taking problems at Kindergarten Imanuel Kedi Halmahera Barat. Data collection techniques were carried out through observation and documentation. The data obtained was analyzed by reducing data. The research results showed that the activity of writing name letters each child can improve the fine motor skills of children in Kindergarten Imanuel Kedi Halmahera barat. this can be seen from the development of students who have experienced an increase from Cycle I of 45.6% and Cycle II of 100%. It can be said that the category is good. This can be seen when the process of learning activities to write the letters of each child's name, children are able to move their fingers and coordinate their eyes.